The complexities of managing forest resources in post-decentralization Indonesia: a case study from Sintang District, West Kalimantan - Yasmi, Yurdi; Anshari, G.Z.; Alqadrie, S.; Budiarto, T.; Ngusmanto; Abidin, P.E.; Komarudin, Heru; McGrath, S.; Zulkifli; Afifudin (Center for International Forestry Research, 2005)
The study attempted to understand the dynamics and complexities of forest resources management following decentralization, the interactions among stakeholders in forest resources management, and the impacts of the new legislation on local community livelihoods in Sintang District, West Kalimantan. Forestry policies implemented in the district before and after the introduction of legislation granting regional autonomy and the emergence of small-scale timber concessions are described. Qualitative research methodologies, i.e. semi-structured interviews, fi eld observations and workshops, were used. The results show that the decentralization of forest management had not proceeded smoothly because of the lack of regulations governing implementation, and that the decentralized forest policies had had both positive and negative impacts. Focusing on 100-ha forest product harvest concessions (HPHH), the study examined opportunities for local communities and other stakeholders to participate in the management of forest resources, the contributions of the small-scale forest concessions to district development and local community livelihoods, and social conflicts arising from a complex combination of factors.